A 47-Year-old Asian female with tracheobronchial space-occupying lesions caused by chronic lymphocytic leukemia - Ji-Wei Zhu; Guo-Hong Cao; Fu-Quan Gao; Zhang Cao; Yan Feng; Hong-Kun Sun; Lu Liu; Pan Xu; Chang-Jun Lv; Lei Pan (BMC Pulmonary Medicine)
Case presentation A 47-year-old Asian woman was admitted with worsening chest tightness and dyspnea for 10 days. Computed tomography (CT) showed changes in the trachea and segmental bronchi. Pulmonary function results suggestive of severe obstructive ventilatory dysfunction. Bronchoscopic findings showed the presence of multiple nodular lesions in the patient’s trachea and left and right main bronchi. Bronchoscopic biopsy, lymph node biopsy and bone marrow aspiration flow cytometry test results led to a definitive diagnosis of chronic lymphocytic leukemia (CLL), staged as Binet stage B and Rai stage 2.